2020
DOI: 10.1088/1361-6463/ab795a
|View full text |Cite
|
Sign up to set email alerts
|

Reactive nitrogen species in plasma-activated water: generation, chemistry and application in agriculture

Abstract: The interest in plasma-activated water (PAW) has been greatly increasing during the last few years due to its potential applications in biological and medical sciences, as well as in agriculture and food industry. The effect of PAW is caused by the reactive oxygen and nitrogen species (RONS) generated in the liquid exposed to plasma. This work reviews recent research on the formation of reactive nitrogen species (RNS) in aqueous solutions treated by non-thermal plasma. The most important chemical reactions lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(130 citation statements)
references
References 136 publications
3
105
0
Order By: Relevance
“…On the other hand, the effect of fosetyl aluminium (FoAl), used as control, was more variable. Moreover, preliminary tests carried out with a synthetic solution with the same concentration of hydrogen peroxide and nitrates and the same pH of PAW, showed the same behaviour of SDW negative control (data not shown), confirming that PAW effect is due to a complex of factors 13 .…”
Section: Figuresupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the effect of fosetyl aluminium (FoAl), used as control, was more variable. Moreover, preliminary tests carried out with a synthetic solution with the same concentration of hydrogen peroxide and nitrates and the same pH of PAW, showed the same behaviour of SDW negative control (data not shown), confirming that PAW effect is due to a complex of factors 13 .…”
Section: Figuresupporting
confidence: 52%
“…The exposure of water to a cold atmospheric pressure plasma induces the production of both reactive oxygen and nitrogen species in the liquid phase, indeed PAW is characterized by the high concentration of long-lived RONS (e.g. hydrogen peroxide and nitrates) that participate in various signalling pathways in plants, which regulate metabolic processes, plant development, and stress responses 13 .…”
mentioning
confidence: 99%
“…[ 40–47 ] Although there are many plasma‐generated species such as superoxide and NO solvate, most are transient species that react to form the end products H 2 O 2 , NO 2 − , and NO 3 − . [ 48 ] Water is introduced in three ways: as part of the feed gas, in contact with the plasma, or exposed to an effluent. Tachibana et al [ 49 ] demonstrated preferential production of NO 2 − , NO 3 − , and H 2 O 2 through feed gas choice or by plasma discharge method.…”
Section: Introductionmentioning
confidence: 99%
“…, and NO 3 − . [48] Water is introduced in three ways: as part of the feed gas, in contact with the plasma, or exposed to an effluent. Tachibana et al [49] demonstrated preferential production of NO and reactive species are produced in direct contact with water.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure of water to cold atmospheric‐pressure plasmas (CAPs) induces different reactive oxygen and nitrogen species (RONS) in the liquid phase, leading to the production of plasma‐activated water (PAW), [ 1‐3 ] and it exerts different effects on biological materials, mainly reduction of the bacterial load, [ 4,5 ] and in the agricultural field, leading to the increase of seed germination, [ 6‐11 ] plant growth, [ 12‐14 ] and induction of disease resistance in plants. [ 15‐17 ]…”
Section: Introductionmentioning
confidence: 99%